IMPLEMENTASI METODE SOFT APPROACH DALAM PROGRAM PEMBINAAN NARAPIDANA TERORISME - Manalu, Paskharia; Siswanto, Heni; Raisa Monica, Dona (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Terrorism is a complex global threat, and its handling requires a comprehensive approach, including the stage of coaching terrorist prisoners (napiter) in correctional institutions (prisons) until reintegration into society. This study aims to analyze the main challenges in implementing the Soft Approach method in the napiter coaching program in Indonesia and explore the potential for utilizing this method to develop a more holistic and sustainable coaching program. The research method used is normative law, by analyzing laws and regulations, legal literature, and other relevant publications. The results of the study identified several significant challenges in implementing the Soft Approach, including the closed and radical attitudes of prisoners, limited human resources and facilities, regulations and institutions that are not yet optimal, resistance to change, and the need for a sustainable approach. Furthermore, this study examines how the humanistic and dialogical principles of the Soft Approach can be utilized to develop a more holistic coaching program, including mental, social, and emotional recovery of prisoners. The development of a sustainable program requires improving the quality of officer resources, provision of facilities and infrastructure, religious reeducation and national insight, development of independence and skills, implementation of social reintegration programs, multi-stakeholder involvement, and ongoing evaluation and monitoring. Thus, this study provides insight into the challenges and potential of the Soft Approach in efforts to provide more effective guidance for terrorist convicts in Indonesia.